`5[3(-90)-45]+5`

Follow order of operations. Therefore we must compute parentheses first.

`5[-270-45]+5`

`5[-315] + 5`

Now mulitply 5 and -315

`-1575 + 5`

`-1570`

**The solution is -1570.**

`5*[3*(-90)-45]+5 =5*[-270-45]+5 =5*(-315)+5 =-1575+5 =-1570`

When computing the above expression we need is to take into account the order of operations unless otherwise specified by the presence of pharantesis. As a general rule, in the same brackets, multiplication (and division) is done first then addition and substraction.

Thus first step is to compute the value of the expression into the square bracket `[3*(-90)-45]`

by computing the result of multiplication: `3*(-90) =-270`

and then the result of substraction: `-270-45 =-315`

Finally, to arrive at the result, we evaluate again first the result of mutiplication of the value of the square bracket `(-315)` with `5` :

`5*(-315) =-1575`

and then we add `5` :

`-1575+5 =-1570`

**Therefore the answer is `5[3*(-90)-45]+5 =-1570` **